PERLINDUNGAN HUKUM TERHADAP PASIEN SEBAGAI KONSUMEN PELAYANAN KESEHATAN NON MEDIS TUKANG GIGI - Feryna, Yohanna; Puspawati, I Gusti Ayu; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Handyman teeth are those who do the work in the sector of dental health, whichdoes not have an official certificate from the Department of Health or educationalinstitution that is recognized by the Department of Health. In addition, Handyman teethdoes not have the provision of dentistry in accordance with medical principles and skillsacquired from generation to decline so it is possible there are many errors andomissions that harm patients. Because the law governing the rights of consumers inIndonesia is not optimally, it is not uncommon that patients be aggrieved without faulton his side in touch with health care providers, almost to say "can not afford" and claimdamages or to enforce their rights.
Keywords: Handyman teeth, Rules of Medical, Law Protection